2011
DOI: 10.1002/ejoc.201101333
|View full text |Cite
|
Sign up to set email alerts
|

A Route to “all‐cis” 2‐Methyl‐6‐Substituted Piperidin‐3‐ol Alkaloids from syn‐(2R,1′S)‐2‐(1‐Dibenzylaminomethyl)epoxide: Rapid Total Synthesis of (+)‐Deoxocassine

Abstract: A general strategy leading to the synthesis of two cis-2-methyl-6-substituted piperidin-3-ols is described. syn-(2R,1ЈS)-2-(1-Dibenzylaminomethyl) epoxide (13) was used as common building block. The key step involved oxirane ring opening of 13 by the nucleophilic lithium aza-enolate of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Subsequent lactam formation gave 152 - 5 in 72% overall yield. This one-pot reductive amination strategy was also employed in the syntheses of (−)-lycojaponicumin C, (+)-1- epi -castanospermine, (+)-deoxocassine, and (+)-dihydropinidine and (−)-pinidinone …”
Section: Reduction Of Imines and Enamines (Figure )mentioning
confidence: 99%
“…Subsequent lactam formation gave 152 - 5 in 72% overall yield. This one-pot reductive amination strategy was also employed in the syntheses of (−)-lycojaponicumin C, (+)-1- epi -castanospermine, (+)-deoxocassine, and (+)-dihydropinidine and (−)-pinidinone …”
Section: Reduction Of Imines and Enamines (Figure )mentioning
confidence: 99%
“…In an earlier study, we reported on the synthesis of α-( S )-dibenzylamino ketones from nonracemic α-bromo-α′-( R )-sulfinyl ketones optically pure only at the sulfur atom ( 1 , Scheme ) via combined in situ substitution–epimerization in a so-called Dynamic Kinetic Resolution (DKR). During the course of that study, a serendipitous discovery was made when the 55:45 epimeric mixtures 1a and 1b , stored for 12 h at 0 °C, precipitated.…”
mentioning
confidence: 99%
“…The physical data were identical in all respect to that previously reported. [9] (E)-6-Bromohex-2-ene (DH02-273-1)…”
Section: (E)-2-(butan-2-ylidene)-11-dimethylhydrazine (Dh02-267-1)mentioning
confidence: 99%